Reliability of a standardized protocol of the Single Leg Heel Rise Test - Anna Schrefl; Nico Kolokythas; Matteo Stamm; Daniel Erlacher; Andrea Schärli (Bern Open Publishing, 2024)
The single leg heel rise (SLHR) test is a widely used method for assessing calf muscle-tendon unit (MTU) endurance in various fields, including medicine, sports, and dance. The objectives of this study were to examine the reliability of a standardized SLHR test protocol with a heel rise measurement device and to investigate the relationship between SLHR repetitions, SLHR total work, and both maximal voluntary isometric contraction (MVIC) and reactive strength index (RSI) outcomes of the plantar flexors. 21 sport students (8 females, 13 males) were assessed for SLHR outcomes (number of repetitions, height of heel rises, total positive work performed) in two data collection sessions, as well as unilateral lower extremity MVIC and RSI. Test-retest reliability showed excellent reliability and low variability for the number of repetitions (Intraclass correlation coefficient (ICC)=0.91, 95% CI: 0.73 to 0.97; coefficient of variability (CV): 8.1- 8.7%), height of the heel rises (ICC=0.92, 95% CI: 0.81 to 0.97; CV: 4.6 - 5.2%) and total positive work performed (ICC=0.96, 95% CI: 0.87 to 0.99; CV: 6.8 - 9.8%) in both feet. No significant correlation was identified between SLHR repetitions, MVIC, and reactive strength outcome measures. A moderate correlation was observed between the total work performed in the SLHR and RSI outcomes that could potentially be explained by the body weight (BW) of the participants. The SLHR test provides reliable measures for lower leg muscular endurance, yet it does not predict plantar flexor maximal strength or reactive strength. In future studies, we advise employing this standardized protocol for screenings of athletes and dancers.